AB0542 Blocking the Human B Lymphocyte Stimulator Molecule (BLYS) Using A Monoclonal Antibody (Belimumab) in Systemic Lupus Erythematosus: First Results in Real-Life Spanish Patients with Refractory Disease (Biogeas-Semi Registry). (10th June 2014) - Brito Zeron, P.; Caminal-Montero, L.; Chamorro, A.; de la Hera Fernández, J.; Gato, A.; Marín-Ballvé, A.; Robles, A.; Rodríguez-Carballeira, M.; Salvador, G.; Saez, L.; Ruiz-Irastorza, G.; Gheitasi, H.; et al.
Abstract : Objectives: To analyze the efficacy and safety of treatment with belimumab, a monoclonal antibody that specifically binds the soluble form of the protein human B lymphocyte stimulator B (BLyS), in SLE patients refractory to standard treatment. Methods: In 2006, the Study Group on Autoimmune Diseases (GEAS) of the Spanish Society of Internal Medicine created the BIOGEAS registry, a multicenter study recruiting patients with refractory systemic autoimmune diseases treated with biological agents. Results: On December 31, 2013, a total of 10 patients treated with belimumab were included in the BIOGEAS Registry, 9 females and 1 male, with a mean age of 41.8 years (range 24-71 years). These patients were heavily treated, with a mean of 7 years of corticosteroid treatment, antimalarials and at least one immunosuppressive agent, mycophenolate in 9, azathioprine in 7, metothrexate in 4, cyclosphosphamide in 2, cyclosporine A in 2, tacrolimus in 2 and talidomide in 2. Belimumab (10mg/kg) was administered in combination with corticosteroids (in all patients), antimalarials (6 patients) and immunosuppressive agents (8 patients, 6 with mycophenolate). The baseline average activity score (SELENA-SLEDAI) was 12 (range 6-33); 8 patients had high titers of anti-dsDNA and/or hypocomplementemia. Therapeutic indication included refractory mucocutaneous involvement (4 patients), refractory vasculitis (3 patients), systemic disease (2 patients) and refractory lupus nephritis (1 patient). After a mean follow-up of 7 months (range 2-12), clinical response could be evaluated in 9 patients, 8 classified as responders (improvement greater than 80% in 5 patients), while the remaining patient was classified as stable. Two patients (20%) developed adverse events (raised transaminases and systemic cryptococcosis due to severe CD4 lymphopenia); there were no deaths or lupus flares. Conclusions: These postmarketing data in Spanish SLE patients in whom belimumab was used following the recommendations approved by the FDA/EMA (refractory disease to standard treatment, clinical and immunological active disease, SELENA-SLEDAI>6) have showed promising results, with a good therapeutic response and a safety profile similar to other biological therapies used off-label in patients with SLE. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5447